Evaluation of prescribing practices and treatment failure for purulent skin and soft tissue infections in patients with obesity - Mackenzie L. Miller; Destiny M. Hughson; Noah D. Blower; Andrew P. Jameson; Lisa E. Dumkow (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract